IMPACT OF IRAN’S CLOSURE AT STRAIT HORMUZ ON UNITED STATE’S SECURITY INTERESTS - Rafa Satya Lanange Hermawan; Siti Fasya Nur Fadhilah; Rizqi Aufa Prawira; Hendra Maujana Saragih (Jurnal Alternatif - Jurnal Ilmu Hubungan Internasional, 2026)
ABSTRACT Iran’s potential closure of the Strait of Hormuz represents a complex strategic issue because it involves not only regional tensions in the Gulf but also energy security, global economic stability, and the national security interests of the United States. As one of the world’s most vital oil transit routes, any disruption in the Strait of Hormuz may trigger rising oil prices, disrupt global supply chains, and intensify geopolitical confrontation. This study aims to analyze how Iran’s strategy of closing the Strait of Hormuz affects the security dynamics of the United States. The research employs a descriptive qualitative method based on library research, drawing on academic literature, policy documents, and relevant sources on Iran-United States relations in the Gulf region. The findings indicate that Iran’s threat in the Strait of Hormuz disrupts U.S. energy security, encourages the United States to increase its military presence in the Gulf through naval patrols and regional security cooperation, and enhances Iran’s geopolitical bargaining position against the United States. Therefore, the Strait of Hormuz functions as a strategic instrument used by Iran to exert political, economic, and military pressure on the United States.